FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN BEROBAT PENDERITA TUBERKULOSIS PARU TAHUN 2017 - Fera ` Meliyanti; Yudi Budianto (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2018)
Based on the number of negative impacts resulting from non-compliance of patients in taking medication, causing new cases findings. The highest recurrence rate of pulmonary tuberculosis patients in Totorejo Health Center with 43 pulmonary tuberculosis patients was 9 patients relapse (20%). The purpose of this research is to know the factors related to the compliance of treatment of Pulmonary TB patient in UPTD Puskesmas Totorejo. The research design used Cross-sectional. The population is all of Pulmonary Tuberculosis patient in UPTD of Totorejo Public Health Center is 51 respondent and sample using the total sample. Analysis of data with univariate and bivariate, statistical test using chi-square. The result of bivariate research shows that there is a significant correlation between knowledge and compliance with treatment of Tuberculosis patients, p-value 0,038; there was significant correlation between attitudes with the compliance of treatment of tuberculosis lung patients, p-value 0,027, there was no significant correlation between the work with the compliance of treatment of lung tuberculosis patients, p-value 0,497, there was a significant correlation between the support of family with the adherence of patients with pulmonary tuberculosis treatment. value 0,021. Berdasarkan banyaknya dampak negatif yang ditimbulkan dari ketidakpatuhan pasien dalam minum obat, menyebabkan angka temuan kasus baru. Tingkat kekambuhan penderita TB paru tertinggi berada di Puskesmas Totorejo dengan 43 penderita TB paru terdapat 9 pasien kambuh (20%). Tujuan penelitian untuk mengetahui faktor-faktor yang berhubungan dengan kepatuhan berobat penderita TB Paru di UPTD Puskesmas Totorejo. Desain penelitian menggunakan Cross sectional. Populasi adalah seluruh penderita Tuberkulosis paru di UPTD Puskesmas Totorejo berjumlah 51 responden dan sampel menggunakan total sampel. Analisa data dengan univariat dan bivariat, uji statistik menggunakan chi square. Hasil penelitian bivariat menunjukkan ada hubungan yang bermakna antara pengetahuan dengan kepatuhan berobat penderita Tuberkulosis paru, p value 0,038; ada hubungan yang bermakna antara sikap dengan kepatuhan berobat penderita Tuberkulosis paru, p value 0,027, tidak ada hubungan yang bermakna antara pekerjaan dengan kepatuhan berobat penderita Tuberkulosis paru, p value 0,497, ada hubungan yang bermakna antara dukungan keluarga dengan kepatuhan berobat penderita Tuberkulosis paru, p value 0,021.